The difference of orphanages' happiness based on gender - Nur Afni Safarina; Nurmaulidina Nasution (INSPIRA: Indonesian Journal of Psychological Research, 2020)
This study aims to determine the differences in happiness in orphanages in terms of gender. This research uses quantitative research methods through a questionnaire for data collection, then a test is carried out to provide an overview of the research variables. The data collection method in this study uses one scale, namely, the scale of happiness. Analysis of data using the T 2 Test Sample Free technique. The participants of this study were 50 children from Miftahul Jannah Orphanage. In terms of the sex of participants for girls taken from the middle-high school range of 25 people, while for men taken from the middle-high school range is as many as 25 people. The results of this study are based on the "Independent Sample Test" output table in the "Equal Variances Assumed" section known to the value of sig. (2-tailed) of 0.83> 0.05. This means there is no difference between man’s happiness and women happiness at the Miftahul Jannah Orphanage.